Some Considerations for Child Rights Impact Assessment (CRIAs) of Business - Collins, Tara; Guevara, Gabrielle (Revue générale de droit, 2014)
With increasing international attention to business and human/child rights, the necessary next step must examine the monitoring of activities in order for the connection between business and child rights to be meaningful. Consequently, the essential question for this paper is whether business should use child rights impact assessments (CRIAs) and if so, what are some considerations in order to move forward? It is argued that the business must develop and carry out CRIAs in order to meet its due diligence obligations, and to identify and respond to potential and actual child rights impacts due to business activities. Business should use CRIAs as part of a broader process of supporting its organizational commitment to human rights. Other actors can also participate in this monitoring endeavour of business activities. This paper identifies some challenges and considerations of CRIAs in relation to business.